Chemopreventive Efficacy of Ginger Extract (Zingiber officinale) - Harliansyah, .; Zurinah, W.N. Wan; Anum, M.Y. Yasmin; Azian, M Noor (Indonesian Research Gateway, 2010)
The liver cells were cultured in theÃÂ presence of ginger extract at various concentrations (0-1 mg /ml) for 24 h and the cells viability and proliferation rate were evaluated by MTS and BrdU assays, whileÃÂ apoptosis was evaluated by colorimetric determination of caspase 8 and 3 activities.ÃÂ Ginger extract exhibited a dose dependent inhibition of viability and proliferation of WRL-68, HLE and HepG2 cells with IC50 of 569.69 ÃÂ± 7.99 ÃÂµg/ml, 389.71 ÃÂ± 26.56 ÃÂµg/ml and 358.71 ÃÂ±ÃÂ 17.12 ÃÂµg/ml respectively. Ginger extract induced apoptosis through activation of caspase-8 and 3 in a dose dependent pattern for all cells at concentration ranging from 0-500ÃÂ ÃÂ¼g/ml.ÃÂ We found that antiproliferative effect of ginger extract could be associated with induction of apoptosis as shown by increased activities of caspase 8 and 3.The results from this study suggest that ginger extract has chemopreventive properties against hepatoma cells HepG2 and HLE by inhibiting cellular proliferation and inducing apoptosis.